The Friday For Future Strategy in Encouraging Public Awareness Of Climate Change Issues in Germany - Herfana, Khafizah; Rijal, Najamuddin Khairur (Universitas Muhammadiyah Surakarta, 2022)
The issue of climate change is a global issue that underlies the Friday for Future movement by Greta Thunberg so as to increase the awareness of teenagers in Germany on environmental issues. However, the role of the Friday for Future (FFF) movement is less effective, because the movement is a Global Civil Society that is independent and has no direct connection with the government. This study aims to determine the strategy of the Friday for Future movement in mitigating climate change. The method in this study uses a descriptive type with a qualitative approach. The data used are primary data from questionnaire results and secondary data through library research, data analysis techniques are deductive techniques. The results showed that the FFF movement strategy consisted of four aspects, namely visibility, in the form of direct action taking to the streets on Fridays, listening aspects by speaking directly with the German Foreign Minister Heiko Maas, lobbying aspects by giving advice and to the government through holidays. every Friday, the networking aspect takes the form of actions at several points in Germany to get more youth involved and online campaigns to garner global support.